Tìm x a) (x – 3)^2 – (x – 3) (x^2 + 3x + 9) + 9(x + 1)^2 =15 b) x(x – 5) (x + 5) – (x – 2) (x^2 + 2x +4) = -17

Question

Tìm x
a) (x – 3)^2 – (x – 3) (x^2 + 3x + 9) + 9(x + 1)^2 =15
b) x(x – 5) (x + 5) – (x – 2) (x^2 + 2x +4) = -17

in progress 0
Margaret 4 tháng 2021-08-25T15:28:00+00:00 2 Answers 5 views 0

Answers ( )

    0
    2021-08-25T15:29:29+00:00

    a) (x – 3)3 – (x – 3)(x2 + 3x + 9) + 9(x + 1)2 = 15

    => (x3 – 9x2 + 27x – 27) – (x3 – 27) + 9(x2 + 2x + 1) = 1

    => x3 – 9x2 + 27x – 27 – x3 + 27 + 9x2 + 18x + 9 = 15

    => 45x + 9 = 15

    => 45x = 15 – 9 = 6

    => x = $\frac{6}{45}$ 

    => x = $\frac{2}{15}$ 

    b) $x\left(x-5\right)\left(x+5\right)-\left(x-2\right)\left(x^2+2x+4\right)=-17$

    $\Rightarrow x\left(x^2-25\right)-\left(x^3-8\right)=-17$

    $\Rightarrow x^3-25x-x^3+8=-17$

    => -25x = -17 – 8 = -25

    => x = (-25) : (-25) = 1

    0
    2021-08-25T15:29:56+00:00

    Đáp án:

     

    Giải thích các bước giải:

    a) $(x – 3)^{3}$ – (x – 3) ($x^{2}$  + 3x + 9) + 9$(x + 1)^{2}$ = 15

    ⇒ $x^{3}$ – 9$x^{2}$ + 27x – 27 – ($x^{3}$ – $3^{3}$) + 9( $x^{2}$ + 2x + 1)= 15

    ⇒ $x^{3}$ – 9$x^{2}$ + 27x – 27 – $x^{3}$ + 27 + 9$x^{2}$ + 18x + 9 = 15

    ⇒ 45x = 15 – 9 – 27 + 27

    ⇒ 45x = 6

    ⇒ x = $\frac{6}{45}$ = $\frac{2}{15}$

        Vậy : x = $\frac{2}{15}$

    b) x(x – 5) (x + 5) – (x – 2) ( $x^{2}$ + 2x + 4) = – 17

    ⇒ x($x^{2}$ – $5^{2}$) – ( $x^{3}$ – $2^{3}$) = – 17

    ⇒ x($x^{2}$ – 25) – $x^{3}$ + 8 = – 17

    ⇒ $x^{3}$ – 25x – $x^{3}$ = -25

    ⇒ – 25x = – 25

    ⇒ x = 1

    Vậy: x = 1

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )